2012
DOI: 10.7314/apjcp.2012.13.5.2185
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Pathogenesis of Barrett's Esophagus in Luoyang, China

Abstract: Background: Prevalence of Barrett's esophagus (BE) in Luoyang, China, has not been reported, and its pathogenesis is controversial. The aim of this study was therefore to investigate the prevalence of BE and its underlying factors in the city of Luoyang. Method: This was a prospective study in one center. Many patients were analyzed using endoscopy who showed upper gastrointestinal symptoms between August 2006 and June 2007. In addition, the effect of apoptosis-related proteins and heat shock proteins upon BE'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Finally, the sections were counterstained with Meyer’s hematoxylin. According to the suggestions of Xu et al [ 32 ] and Zhang et al [ 33 ], we used IS to assess the staining results in this study: IS = the percentages of positive cells × standard scores of the staining intensity. The relative populations of the positive cells were assessed under the same objective: Negative, 0 points; ≤10%, 1 point; 11%–50%, 2 points; 51%–75%, 3 points; and >75%, 4 points.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the sections were counterstained with Meyer’s hematoxylin. According to the suggestions of Xu et al [ 32 ] and Zhang et al [ 33 ], we used IS to assess the staining results in this study: IS = the percentages of positive cells × standard scores of the staining intensity. The relative populations of the positive cells were assessed under the same objective: Negative, 0 points; ≤10%, 1 point; 11%–50%, 2 points; 51%–75%, 3 points; and >75%, 4 points.…”
Section: Methodsmentioning
confidence: 99%
“…Although the HSP 27 has a significant role in esophagitis, Zhang et al [ 31 ], evaluating patients with esophagitis with and without Barrett’s esophagus, showed that the expression of HSP 27 seems to remain unaltered [ 31 ]. However, patients with Barrett’s esophagus had significantly lower expression of HSP 70 and HSP 90α than patients with esophagitis without Barrett’s esophagus [ 31 ]. In Zhang et al’s study [ 31 ], the telomerase reverse transcriptase (TERT) expression was also reduced in Barrett’s esophagus.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, patients with Barrett’s esophagus had significantly lower expression of HSP 70 and HSP 90α than patients with esophagitis without Barrett’s esophagus [ 31 ]. In Zhang et al’s study [ 31 ], the telomerase reverse transcriptase (TERT) expression was also reduced in Barrett’s esophagus. The HSP 105 and the Caspase-3 expressions are increased when comparing Barrett epithelium to esophagitis without Barrett’s [ 31 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In the studies performed on patients with GERD or any gastrointestinal system complaint in the countries to the east of Turkey, the prevalence of ERD was between 3.4% and 66.5% (37,38) and the histopathological prevalence of BE was between 0.3% and 7.3% (39)(40)(41)(42)(43). On the other hand, in a study conducted in Japan, the rate of patients that were endoscopically diagnosed with BE was reported to be 37.6%.…”
Section: The Epidemiology Of Gerd Complications In Turkey and Around mentioning
confidence: 99%